Determinan Return on Equity pada Bank Pembangunan Daerah di Kalimantan - Hayet, Hayet; Ayuni, Hesti Diah; Deffrinica, Deffrinica (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
To maintain stability and enhance profitability, banking institutions must carefully manage key internal performance indicators, including interest-generating capacity, capital adequacy, and credit quality. This study aims to analyze the effect of Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), and Non-Performing Loan (NPL) on Return on Equity (ROE) at regional development banks in Kalimantan during the 2016–2025 period. Utilizing secondary data sourced from annual financial reports published by the Financial Services Authority (OJK) and respective bank websites, this research employs panel data regression, with the Common Effect Model (CEM) identified as the most appropriate estimation method. The empirical results demonstrate that NIM exerts a positive and significant effect on ROE, indicating that a bank’s heightened capacity to generate net interest income directly drives profitability. Conversely, both CAR and NPL exert negative and significant effects on ROE. This suggests that excessive capital adequacy, when not accompanied by optimal productive asset allocation, alongside rising non-performing loans, substantially diminishes banking profitability. Jointly, all independent variables exhibit a significant simultaneous effect on ROE within the observed regional development banks.